A new method for investigating the relationship between diet and mortality: hazard analysis using dietary isotopes - R. C. Redfern; S. N. DeWitte; J. Beaumont; A. R. Millard; C. Hamlin (Taylor & Francis Group, 2019)
Background: The population of Roman Britain are renowned for having elevated nitrogen (δ15) stable isotope values, which have been interpreted as evidence for the increased consumption of marine products. However, such results are now understood to also reflect episodes of stress and disease, suggesting that new interpretations are warranted. Aim: To test a novel approach which combines hazard mortality analysis and stable isotope data to determine whether there is a relationship between age-at-death, elevated δ15N values and mortality risk. Subjects and methods: This study used published osteological and dietary stable isotope data for nitrogen (δ15N) and carbon (δ13C) of 659 1st-5th century AD individuals aged >12 years old excavated from Roman cemeteries in Britain. The relationship between diet and mortality risk was assessed using the Gompertz hazard model, and differences in median reported isotope values between the sexes was determined using a Mann Whitney test. Results: It was discovered that higher δ15N levels are associated with elevated risks of mortality, whereas the opposite pattern was observed for δ13C, and males had higher median δ13C and δ15N values. Conclusion: This study successfully demonstrated that stable isotope data can be integrated into hazard models, allowing one to connect diet and mortality in past populations. It supports the findings of other isotope studies which have established that individuals with childhood stress/trauma will have different isotope patterns.